Vaginal pH Value for Clinical Diagnosis and Treatment of Common Vaginitis - Yen-Pin Lin (MDPI AG, 2021)
In modern society, 75% of all women worldwide have had vaginitis at least once in their lives. The vagina has a dynamic microbial ecosystem with varying vaginal pH levels. An imbalance in that ecosystem can alter the vaginal pH and tip the scale to the point of causing issues, such as vaginitis, that require medical attention. Although vaginitis is not an incurable disease, it causes discomfort and pain that disrupt women’s daily lives. The most common causes of vaginitis include bacterial vaginosis, trichomoniasis, and vulvovaginal candidiasis. In this review, we discuss the causes, diagnostic methods, and symptoms of different types of vaginitis, the relationship of vaginitis to the prevalence of other diseases, issues associated with recurrent vaginitis and the immune system, and a variety of effective available treatments. In our article, we summarize the relationship of pH with the vaginal ecosystem, discuss the associated factors of vaginal pH, and finally introduce the different available vaginal pH self-test products.